(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the use of α-adrenergic blockers in the treatment of acute urinary retention (AUR), a serious complication of benign prostatic hyperplasia (BPH). It highlights clinical findings regarding silodosin, a new generation uroselective α-blocker approved for managing lower urinary tract symptoms due to BPH. Silodosin is distinguished by its high degree of uroselectivity, fast therapeutic onset, and ease of use—a standard 8 mg daily dose that remains consistent regardless of patient age. Furthermore, it is compatible with concurrent use of antihypertensive therapies.